PERSEPSI WARGA BINAAN PEMASYARAKATAN TERHADAP KESANTUNAN BERBAHASA DI LAPAS PEREMPUAN KELAS IIA SUNGGUMINASA - Hasbi, Andi Erwin Chandra; Yassi, Abdul Hakim; Gusnawaty, Gusnawaty (Neologia: Jurnal Bahasa dan Sastra Indonesia, 2021)
This study aims to obtain an in- depth description of the actual conditions in which prisoners' language is used. The data in this study are prisoners' perceptions of language politeness which were collected based on the results of a questionnaire survey in the field from 72 respondents from prisoners. The type of research used in this study is qualitative with a descriptive-qualitative approach. The results of this study indicate that the perception of prisoners in the Class IIA Sungguminasa Women's Prison towards the use of polite language is quite high, which is around 85% but in its use it is also often used harsh language by 82% of all inmates at the Class IIA Sungguminasa Women's Prison.